Feast of the Pheasant in 1454 (engraving) - Édouard Riou (Wikimedia Commons, 1860)
Notice iconographique issue de Wikimedia Commons. Titre: Feast of the Pheasant in 1454 (engraving). Feast of the Pheasant in 1454 (engraving)
Droits : Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; Patrimoine; Wikimedia Commons; Iconographie